Nutritional Habits and Interventions in Childhood - Scaglioni, Silvia; Mazzocchi, Alessandra; De Cosmi, Valentina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The objective of this book is to present nutritional and educational interventions for children and their families. The creation of healthy preferences is a key determinant of food choices and therefore diet quality. Food choices have important implications for health, particularly for food-related diseases, such as feeding difficulties and the development of non-communicable diseases. The first years of a child's life are fundamental for the creation of tastes, eating habits and the relationship with food. Preferences for certain foods are neither innate nor unchangeable. Eating behaviour is the result of experience and learning, and, through the repeated offering of food by parents, especially those less accepted, it is possible to promote good nutrition. Behaviour depends on the interaction of environmental factors, genetics, sex, and age. The environment in which the child is immersed, and which influences them, includes family, other children, society, media and the supply of food. Achieving an adequate intake of macro and micro-nutrients is an important objective for all ages of life and, particularly, for those of pediatric age, since it is crucial for cognitive development. Nutrition has also a therapeutic effect. Nutritional interventions tailored to specific pathologies are needed to prevent nutritional deficiencies and maintain an adequate nutritional status, since children and adolescents with chronic or inflammatory diseases are particularly vulnerable and at major risk of developing malnutrition.